Service-O-meter car maintenance reminder / Ayu Ismail - Ismail, Ayu (2006)
Most of the car components' may deteriorate over a certain period of time. Therefore, proper car maintenance is necessary in order to preserve the lifetime of the car parts. All cars come with their maintenance manuals, but most people tend to ignore it. Moreover, due to lack of information on this matter, some people do not even know how to maintain their own car. In order to overcome these problems, an electronic device that can calculate the components' replacement schedule based on the mileage and give good tips to the owners is designed. This device is called Service-O-Meter whereby it uses PIC16F877A microcontroller by Microchip as the brain. In this thesis, the whole project will be described briefly in each chapter. In Chapter 2, the theoretical aspect regarding the PIC16F877A microcontroller, LCD and voltage regulator will be presented and explained for further understanding. The Service-O-Meter hardware design is elaborated and the technical aspects are explained with the help of the schematic design in Chapter 3. In addition, the fabrication process is also discussed. Software is dedicated for Chapter 4. Furthermore, the results and discussions on the experiment done are analyzed in Chapter 5. Finally, the conclusion and future developments are presented in Chapter 6.